DETERMINAN FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI IBU HAMIL MELAKUKAN PEMERIKSAAN HIV/AIDS - Herniwati Herniwati; Adius Kusnan; La Ode Muh. Sety (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Human Immunodeficiency Virus (HIV) is a virus that can infect white blood cells which causes a decrease in the human immune system. This study aims to analyze factors related to the motivation of pregnant women to carry out HIV/AIDS examinations in the work area of the Health Office of North Buton Regency. This type of research is analytic observational using a cross sectional study design which was carried out in the work area of the North Buton District Health Office, in February-March 2022 involving 82 respondents. The statistical tests used were chi square and logistic regression. The results showed that the most dominant mother's motivation was in the good category as many as 71 respondents (86.6%), and the least was the poor category as many as 11 respondents (13.4%). The fisher exact test results obtained a p-value of 0.025 <0.05, meaning that there is a relationship between knowledge and mother's motivation, fisher's exact test obtained a p-value of 0.000 <0.05, There is a relationship between the competence of health workers with mother's motivation (p-value = 0.017). Motivation of pregnant women to do HIV AIDS testing is related to the knowledge and competence of the officers